2007
DOI: 10.1111/j.1600-0501.2006.01308.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased bone formation to unstable nano rough titanium implants

Abstract: Early bone response to cylindrical smooth titanium implants (S(a)=0.1 microm) inserted into the rabbit tibia was compared in a stable and nonstable regime. Surface roughness parameters were calculated from measurements obtained with optical interferometry and atomic force microscopy. Contrary to our hypothesis, the nonstable implant showed higher bone to metal contact and increased bone area in the endosteal region compared with the stable implant after 4 weeks of healing. Bone area measurements in the cortica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
2
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 18 publications
1
56
2
1
Order By: Relevance
“…However, initial clinical stability may require additional considerations of micron-scale topography and overall implant design. The pioneering investigations of Meirelles and co-workers [148,149] suggest that nanometer-scale topography alone is not sufficient to assure robust osseointegration. Investigations which have isolated nanometer-scale topography as an experimental variable in osseointegration have required additional consideration of endosseous implant stability.…”
Section: The Relative Value Of Nanoscale and Micron-scale Roughnessmentioning
confidence: 99%
See 1 more Smart Citation
“…However, initial clinical stability may require additional considerations of micron-scale topography and overall implant design. The pioneering investigations of Meirelles and co-workers [148,149] suggest that nanometer-scale topography alone is not sufficient to assure robust osseointegration. Investigations which have isolated nanometer-scale topography as an experimental variable in osseointegration have required additional consideration of endosseous implant stability.…”
Section: The Relative Value Of Nanoscale and Micron-scale Roughnessmentioning
confidence: 99%
“…Increased bone formation was measured for nanoscale rough implant surfaces in animal models [148]. In a series of studies the same group found early bone formation and increased torque removal when implant surfaces were added with nano-hydroxyapatite or titania [149].…”
Section: Differentiationmentioning
confidence: 99%
“…24,54 One factor that can improve and accelerate the osseointegration of an implant is surface nanotopography. 55,56 …”
Section: Biocompatibility and Osseointegrationmentioning
confidence: 99%
“…Such contradictory results between in vivo and in vitro experiments may be explained via the theory proposed by Meirellese et al 30 who considered that nanoscale topography alone is not sufficient to assure robust osseointegration; favorable osseointegration requires additional considerations of microscale topography and overall implant design for initial clinical stability.…”
mentioning
confidence: 99%